1999
DOI: 10.1007/bf03013194
|View full text |Cite
|
Sign up to set email alerts
|

Topical amethocaine (Ametop™) is superior to EMLA for intravenous cannulation

Abstract: Purpose: A eutectic mixture of local anesthetics (EMLA) is commonly used to provide topical anesthesia for intravenous (iv) cannulation. One of its side effects is vasoconstriction, which may render cannulation more difficult. A gel formulation of amethocaine (Ametop") is now commercially available. The aim of this study was to compare EMLA and Ametop TM with regard to the degree of topical anesthesia afforded, the incidence of vasoconstriction and the ease of iv cannulation. Methods: Thirty two ASAI adult vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 28 publications
1
35
1
2
Order By: Relevance
“…Speirs et al 21 found topical tetracaine to provide greater analgesia than EMLA, but the difference in visual analogue scale scores was not statistically significant. The remaining 3 trials 22,44,45 concluded that topical tetracaine provides significantly greater anesthesia than EMLA.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Speirs et al 21 found topical tetracaine to provide greater analgesia than EMLA, but the difference in visual analogue scale scores was not statistically significant. The remaining 3 trials 22,44,45 concluded that topical tetracaine provides significantly greater anesthesia than EMLA.…”
Section: Resultsmentioning
confidence: 97%
“…The study involved 100 adults undergoing radial artery puncture and found comparable efficacy between the 2 forms of anesthesia. Four other randomized, controlled trials compared either tetracaine 4% gel 21,44,45 or tetracaine 5% cream 22 with EMLA cream. The procedure in each trial was intravenous cannulation.…”
Section: Resultsmentioning
confidence: 98%
“…Damar yolu açma öncesi lokal ilaç uygulamanın dezavantajları ise yan etki ihtimali ve ek maliyettir. Lidokain+prilokain kremin önce vazokonstrüksiyon, uygulamanın 180. dakikası sonrası ise vazodilatasyona neden olduğu bilinmektedir (12)(13)(14)(15). Bu durum girişimin başarısızlıkla sonuçlanabileceğini düşündürmekle birlikte çalışmalarda iv kanülasyonu güçleştirdiği saptanmamıştır.…”
Section: Discussionunclassified
“…Browne et al (1999) compared the superiority of ametop in relation to EMLA for its use in intravenous cannulation. This study found that intravenous cannulation was less painful following the application of ametop in comparison to EMLA.…”
Section: Ametopmentioning
confidence: 99%